2023
DOI: 10.1002/fsn3.3527
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of food security status of household in west Gojjam zone, Ethiopia

Abstract: Food security is based on a variety of factors, including how well agricultural production is doing, how much food we import, how many people are employed in the food industry, what public policies are put in place to improve food production strategy and food security of the household. Food is important for human beings so that everyone can have enough of it. A lack of food in the long term can lead to people becoming hungry and starving, which can be dangerous. There are many ways to boost food production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(35 reference statements)
1
1
0
1
Order By: Relevance
“…This could be because working off-farm generates extra income in addition to farm income, increasing household income diversity and food security. This is consistent with studies conducted by Danso-Abbeam et al ( 2023), Assefa and Beyene (2023) and Worku (2023). Furthermore, information-related assets such as mobile phones, television, or radio reduce the likelihood of households experiencing severe food insecurity while increasing the likelihood of food security status among farming households.…”
Section: Association Between Food Security and Household Characteristicssupporting
confidence: 91%
“…This could be because working off-farm generates extra income in addition to farm income, increasing household income diversity and food security. This is consistent with studies conducted by Danso-Abbeam et al ( 2023), Assefa and Beyene (2023) and Worku (2023). Furthermore, information-related assets such as mobile phones, television, or radio reduce the likelihood of households experiencing severe food insecurity while increasing the likelihood of food security status among farming households.…”
Section: Association Between Food Security and Household Characteristicssupporting
confidence: 91%
“…The study by [46] concluded that farmers' households with both on-farm and non-farm income are more likely to be food secure than farmers' households relying solely on agriculture. Non-farm income positively impacts the household's food security [47].…”
Section: Resultsmentioning
confidence: 99%
“…This study contradicts the notion that households with a larger number of family members are more likely to be food secure. This is because they have more food to share, making it less likely that someone in the household will be starving [47], [53], [54].…”
Section: Resultsmentioning
confidence: 99%
“…Our specific objectives were (1) to measure the prevalence of Household Food Insecurity (access) in NLGA; (2) to examine factors associated with household food security in the locality; and (3) to explore household dietary diversity. This research is vital as there is a continuing debate on the gender of household head and household food security level (Adepoju & Adejare, 2013 ; Felker‐Kantor & Wood, 2012 ; Matemilola & Elegbede, 2017 ; Nwaka et al, 2020 ) and age impact on food security (Department of Environmental, Food and Rural Affairs, 2021 ; Worku, 2023 ). This information is important to inform the policy direction for the alleviation of food insecurity in this region.…”
Section: Introductionmentioning
confidence: 99%